The Impact of the Rise of Chinese Power on the Change in Japanese Foreign Policy - Abdel-Aziz, Ghzlan Mahmoud (Dirasat: Human and Social Sciences, 2025)
Objectives; This study aims to examine the potential shift of Japan's foreign policy, utilizing a more balanced strategy towards China's rise to power. It investigates a number of hypotheses inscribing state behavior towards rising powers as stipulated in international relations theories including realism, structural-liberalism, offensive realism, defensive realism, and neo-classical realism. The study analyzes Japan's foreign policy towards China’s rise to power and the factors contributing to the critical change in Japan’s defense policy. Methodology; The study employs David Easton's political system theory, Preacher’s model of foreign policy and the national interest approach as it relevant to power politics. Results; The findings suggest a notable shift in Japan's strategy towards China’s rise to power, adopting active balancing through active diplomatic encirclement. Conclusion; The study concludes that changes in the regional and international order have influenced Japan's foreign policy towards China, transitioning from hedging to active balancing.